Impact of Mass Media on Rural Women – A Sociological Study: Exploring the Challenges Faced by Rural Women in India (Journal of Advances and Scholarly Researches in Allied Education, 2019)
India is a village nation where poverty rates are high. The rural women are in a position of greatest burden. Roughly 81 per cent of the nation's estimated female population lives in rural areas. Even after 70 years of independence, in fact, women continue to be marginalized with an unequal financial and political status. Its productive and regenerative sections remain largely imperceptible. Despite constitutional recognition of equal rights and benefits, there is no special case for Indian women in those worlds. In this way the importance of gender orientation and the affirmation of women has become an imperative topic of open deliberation in India's formative projects, particularly in the last few decades.